Factors influencing medical academics’ intention to stay - Abdul Malek, A Tambi; Mohamad Zulkifli, Abdul Rahim; Rabiatul Adawiyah, Muslim; Mardziah Hanim, Mahzir; Noormahayu, Mohd Nasir; Nur Lailatul Husna, Mohammad Yusof (2017)
The Ministry of Higher Education in Malaysia were alarmed by the high attrition rate of medical academic staff at public higher education institutions. They responded by setting up a high-level committee to look into improving the conditions for medical lecturers in the public service. The objectives of the research were to identify the factors that influence medical academics’ intention to stay with their job and determine the strength of their influence. The corresponding research questions were: (1) What factors influenced medical academics’ intention to stay? and (2) What was the strength of their influence?